2019
DOI: 10.1097/opx.0000000000001407
|View full text |Cite
|
Sign up to set email alerts
|

Visual Deficits and Dysfunctions Associated with Traumatic Brain Injury: A Systematic Review and Meta-analysis

Abstract: SIGNIFICANCE:This study reports prevalence data combined independently for accommodative dysfunction, convergence insufficiency, visual field loss, and visual acuity loss in patients with traumatic brain injury in the absence of eye injury. OBJECTIVE:The objective of this study was to conduct a systematic review and meta-analysis to determine the prevalence rates of accommodative dysfunction, convergence insufficiency, visual field loss, and visual acuity loss in TBI patients without concomitant eye injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 72 publications
2
40
0
2
Order By: Relevance
“…All measurements showed a high rate of visual dysfunctions. This is in agreement with previous studies and other studies concerning frequencies of visual impairment and dysfunction after stroke or TBI (Berthold‐Lindstedt et al., 2017; Ciuffreda et al., 2007; Merezhinskaya et al., 2019; Rowe et al., 2009; Schuett et al., 2012) and indicate the need of a visual assessment and rehabilitation based on the patient's capacity of processing visual information.…”
Section: Discussionsupporting
confidence: 92%
“…All measurements showed a high rate of visual dysfunctions. This is in agreement with previous studies and other studies concerning frequencies of visual impairment and dysfunction after stroke or TBI (Berthold‐Lindstedt et al., 2017; Ciuffreda et al., 2007; Merezhinskaya et al., 2019; Rowe et al., 2009; Schuett et al., 2012) and indicate the need of a visual assessment and rehabilitation based on the patient's capacity of processing visual information.…”
Section: Discussionsupporting
confidence: 92%
“…About 25% of the sample had been diagnosed with convergence insufficiency and ∼23% with accommodative insufficiency, suggesting damage to visual detection pathways. Such visual detection impairments, including visual field loss, have higher prevalence in msTBI than in mTBI, and can be detected after both blast-induced (military) and non-blast-related (civilian) mTBI ( Capó-Aponte et al, 2017 ; Merezhinskaya et al, 2019 ). Commonly reported deficits of higher-order visual processing include impairments related to form recognition, motion perception, and figure/ground discrimination ( Ciuffreda et al, 2016 ; Alnawmasi et al, 2019 ).…”
Section: Perceptual-motor Functionmentioning
confidence: 99%
“…40 A metaanalysis concluded that convergence insufficiency occurs in 37% of patients with mTBI. 18 Detailed studies have showed that dynamic vergence measures are reduced, 41 and vergence instability may be reflected in greater horizontal disconjugacy during naturalistic viewing. 42 Pursuit of a predictably moving target was reduced in some studies [43][44][45] but others found little change.…”
Section: Ocular Motor Dysfunction In Traumatic Brain Injurymentioning
confidence: 99%
“…70 Accommodative problems occur with mTBI, 71 with a meta-analysis suggesting a prevalence of about 40%. 18 For these reasons, current vision therapy protocols often include accommodative training. 70,72,73 Compared with vergence therapy, less is known about the effects of accommodative training.…”
Section: Training Of Vergence Eye Movementsmentioning
confidence: 99%
See 1 more Smart Citation